Multi-marker comparative analysis of 18S, ITS1, and ITS2 primers for human gut mycobiome profiling - Orsud, Hiba; Zoughbor, Sumaya; AlDhaheri, Fatima; Hajissa, Khalid; Refaey, Manar; Ajab, Suad; Alswaider, Khaled; Mohamed, Nora; Alkaabi, Obaid; Al Rasbi, Zakeya (Frontiers in Bioinformatics, 2025)
BackgroundGut fungi play crucial roles in human health. The profiling of the human gut mycobiome continues to progress. However, adjustments in the selection of ribosomal DNA marker regions can substantially affect the taxonomic resolution of a population. In particular, the impact of using primers’ combinations is insufficiently defined. In this study, we investigated the performance of three targeted sequencing regions, ITS1, ITS2 and 18S rRNA, separately and in combination.MethodsEight fecal samples from healthy individuals (n = 4) and cancer patients (n = 4) were selected as proof of principle for amplicon-based sequencing conducted with the DNBSEQ™ sequencing system. Quality-filtered reads were grouped into operational taxonomic units (OTUs) via USEARCH and categorized using the SILVA (18S) and UNITE (ITS) databases. Downstream bioinformatics encompassed diversity analyses, principal component analysis (PCA), and biomarker detection via linear discriminant analysis effect size (LEfSe). To improve taxonomic coverage and compositional understanding, data were examined using ALDEx2 with centered log-ratio (CLR) transformation, facilitating reliable differential abundance and effect size assessment in small sample metagenomic contexts.Results and DiscussionAmong primers, ITS2 and ITS1 enhanced the coverage of identified taxa, with operational taxonomic unit quantities of 183 and 158, respectively, compared to 58 OTUs of 18S. Accordingly, among primer combinations tested, the triple integration of ITS1–ITS2–18S produced the highest fungal richness, while the dual ITS1–ITS2 combined datasets enhanced group discrimination analysis, showing enrichment of Candida albicans and scarcity of Penicillium sp. in cancer patients. Our findings based on ITS sequencing and the combination of ITS1 and ITS2 provide instructive information on the composition and dynamics of gut fungi in our initial test subjects, enhancing our understanding of their roles in gut homeostasis and the microbial shifts associated with cancer. Despite our approach being conducted with a limited cohort to establish methodological feasibility, it brings attention to multi-marker strategies, demonstrating that integrated primer datasets surpass traditional single-marker methods in both taxonomic coverage and biomarker detection sensitivity in low-biomass fecal samples. Our research provides a reliable starting point for future studies on gut mycobiome in both healthy and diseased individuals, which could lead to better diagnostics and treatments based on microbiome profiles.